Analisis Pelaksanaan ART Dan PrEP Dalam Membendung HIV: Perspektif Syariah - Mohd Harifadilah Rosidi; Abdul Manan Ismail; Ahmad Wifaq Mokhtar (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus/MyCite